Study of the association of polymorphisms of the folate cycle enzyme gene with the degree of cognitive and affective disorders in patients in the post-covid period - A.A. Shuprovych; O.V. Zinych; N.M. Kushnareva; O.M. Trofymenko; K.P. Komisarenko (Medičnì Perspektivi)
Recently, molecular genetic studies have become widespread, and demonstrated the importance of DNA and histone methylation processes in the epigenetic regulation of gene expression. The aim of this study was to detect the association of polymorphisms of the folate cycle enzyme gene methylenetetrahydrofolate reductase (MTHGFR) with the degree of cognitive and affective disorders and the serum level of homocysteine and folic acid in 41 post-covid patients. Hematological and laboratory indices, serum concentration of C-reactive protein, D-dimer, homocysteine and folic acid were determined. MTHGFR polymorphisms for C677T and A1298C mutations were determined by polymerase chain reaction in real time. According to the MTHGFR C677T genotype variant, the examined patients were divided into 3 groups: 1) 21 persons (male/female 10/11) with homozygous CC genotype; 2) 17 ones (male/female 12/5) with heterozygous CT genotype; 3) 3 persons with a recessive homozygous TT genotype (all men). Six months after the end of the acute phase of the coronavirus disease, patients were surveyed using questionnaires to assess the psycho-emotional state: cognitive function, anxiety and depression. No significant difference was found in the average scores of cognitive function, anxiety and depression in patients of group 1 and 2. Individuals of the group 1 C677C, who had an additional recessive homozygous C1298C mutation (group 1a, n=6), were characterized by an elevated level of homocysteine, which showed a high negative correlation with serum folate (r= -0.95). A small group of individuals with the recessive homozygous T677T genotype (group 3, all men) was distinguished by an older age, the presence of cardiovascular diseases, type 2 diabetes (2 cases out of 3), more severe manifestations of COVID-19, which forces us to pay attention to potentially increased risk of complications in such patients and requires further investigation. Correlation relationships between assessments of cognitive function, anxiety, depression and serum levels of homocysteine and folate in patients with different genotypes of MTHGFR C677T were recorded. Therefore, the use of a molecular genetic approach made it possible to pay attention to the possible predisposition to hyperhomocysteinemia in individuals who have a folic acid deficiency, and different combination of alleles of the MTHGFR gene C677T and A1298C.